K Problem Solving Ability on Independent Learning and Problem Based Learning with Based Modules Ethnomatematics Nuance - Bahri, Silvi Prisha; Zaenuri, Zaenuri; Sukestiyarno, YI (Unnes Journal of Mathematics Education Research, 2018)
The purpose of this study was 1) to know the effectiveness of independent learning and Problem Based Learning models with the nuances of Malay culture based modules in improving students' problem solving abilities in quadrilateral material, 2) to know problem solving abilities of students taught by using independent learning and Problem Based Learning with the nuances of Malay culture based modules on the development of character of love for local culture. This study applied mixed methods method. The study was conducted in grade VII of SMP N 1 Bintan 1 and SMP N 2 Bintan in the academic year of 2017/ 2018 school, where both of them was taken as the experimental classes on triangular and quadrilateral material. Data collection was done by using tests, questionnaires and interviews. The results showed that 1) independent learning and Problem Based Learning with the nuances of Malay culture based modules were effective in improving the problem solving abilities indicated by (a) students problem solving abilities achieving the minimum classical completeness criteria, (b) the average of students' problem solving abilities exceeded the KKM which are given. (c) there is no difference between independent learning and Problem Based Learning models with Malay culture nuances on average. (d) there is an increase in the problem solving ability of students and a sense of love of students on culture after learning. 2) There is an increase in the character of cultural love that can improve students' problem solving abilities.